Diagnostic Challenges of Helicobacter pylori Infection in Ethiopia: A Community-Based Cross-Sectional Study. (2nd June 2022) - Gudina, Esayas Kebede; Amare, Hiwot; Ali, Solomon; Berhane Arefayine, Melkamu; Tewolde, Dagmawi; Tesfaye Eshete, Million; Jebena, Mulusew Gerbaba; Wieser, Andreas; Froeschl, Guenter; Tesfaye, Markos; Desalegn, Hailemichael; Gashaw, Mulatu
Abstract : Background . In resource-constrained countries, accurate diagnosis of Helicobacter pylori infection remains a challenge. This study aimed to assess the clinical utility of locally available serological and stool antigen test kits in the management of people with suspected H. pylori infection in Ethiopia. Methods . A community-based cross-sectional study was conducted with apparently healthy adults and children living in southwest Ethiopia. Participants were interviewed for dyspepsia symptoms and related clinical conditions. H. pylori infection was examined using commercially available serological and stool antigen tests. The association between H. pylori tests and dyspepsia symptoms was analyzed using logistic regression models. Results . Out of 1392 participants included in the final analysis, 49.1% and 6.5% tested positive for H. pylori infection with serology and stool antigen test kits, respectively. Participants reporting epigastric symptoms in the past three months (AOR = 1.93, 95% CI = 1.28–2.91) and those with recent dyspepsia treatment (AOR = 1.51, 95% CI = 1.05–2.18) were likely to have positive serology test. However, no association between dyspepsia symptoms and H. pylori stool antigen positivity was observed in our study. Conclusion . ccurate detection of H. pylori infections using commercially accessible diagnostics remains difficult in Ethiopia. With these methods, it will be hard to ensure adequate diagnosis and early treatment of H. pylori infection, as well as rational antibiotic use.